Nutrient analysis of sandladen dairy manure - Strahm, T.; Harner, Joseph P.; Key, David V.; Murphy, James P. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Nine concrete storage basins were sampled on Kansas dairies and analyzed for nutrient content of sand-laden dairy manure. The manure average 75% moisture content during the three sampling periods. The average total nitrogen, phosphate, and potash were 9.7, 4.6, and 7.4 lb/ton, respectively. The data collected from the basin indicated that when the scraped manure from a dairy is applied at an agronomic rate of 15 tons or less per acre, accumulation of nutrients should be minimal, in particular phosphorus. The manure value was $3 to $4 per ton depending on whether commercial sources of phosphorus normally would be applied to the cropland.
Keywords: Dairy; Manure; Nutrients; Sand